A Multicenter Retrospective Study on Magnitude, Distribution, Socio-Demographic, and other Risk Factors Associated with Hemodialysis in Jigawa State, Northwest Nigeria - Ibrahim, Usman; Abdulsalam, Kabiru; Sidi, Kamalu; Lawrence, Ademola; Buba, Luka; Muazu, Salisu; Zubairu, Zahrau; Jalo, Rabiu; Aliyu, Muhammad; Bashir, Usman; Jibo, Abubakar; Karkarna, Mustapha (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: There is a growing concern regarding increasing cases of kidney diseases in Jigawa state, with most conditions requiring hemodialysis or other forms of renal replacement therapy.Aim: This study aimed to find the magnitude, distribution, socio-demographic, and other factors associated with hemodialysis in Jigawa state, Northwest Nigeria.Materials and Methods: It was a retrospective multicenter analysis of secondary data from hemodialysis centers of the randomly selected public hospitals in northwest Nigeria.Statistical Analysis: Data were analyzed using IBM SPSS Statistics for Windows, version 22.0, with statistical significance set atP≤ 0.05.Results: A total of 1,329 patients were enrolled for dialysis in Kano and Jigawa states, between 2019 and 2022, out of which more than one-third (509, 38.3%) were from Jigawa state. Dutse, Jahun, Gumel, and Hadejia local government areas (LGAs) of Jigawa state had 86 (16.8%), 64 (12.6%), 48 (9.4%), and 44 (8.6%) respectively. The respondent's ages ranged from 1 − 100 years with a median age of 48 (interquartile range [IQR] = 31, 60) years. Chronic kidney disease (CKD) was found among 403 (79.2%) patients, acute on chronic kidney disease (AOCCKD) in 87 (17.1%) patients, and acute kidney injury (AKI) in 19 (3.7%) patients. The major risk factors identified were hypertension, diabetes, and chronic glomerulonephritis (CGN) among 329 (64.6%), 69 (13.6%), and 66 (13.0%) patients, respectively. Hypertension was a significantly higher risk factor among patients from Jigawa state compared with other states (46.8%,P< 0.001), hypertensives from Jigawa state were twice more likely to develop kidney disease requiring hemodialysis (adjusted odds ratio [aOR] = 2.2, 95% confidence interval [CI] = 1.7–2.8) compared with non-hypertensive etiologies.Conclusion: The burden of kidney diseases requiring hemodialysis in Jigawa state is high, with hypertension and diabetes being the major risk factors for hemodialysis. The government and other stakeholders should develop strategies for early identification and proper management of the risk factors.
Keywords: Hemodialysis; Nigeria; Northwest; risk factors; socio‑demographic factors